Determinants of Job Satisfaction across the EU-15: A Comparison of Self-Employed and Paid Employees - Jose Maria Millan; Jolanda Hessels; Roy Thurik; Rafael Aguado (Tinbergen Institute, 2011)
Job satisfaction of self-employed and paid-employed workers is analyzed using the European Community Household Panel for the EU-15 covering the years 1994-2001. We distinguish between two types of job satisfaction, i.e. job satisfaction in terms of type of work and job satisfaction in terms of job security. Findings from our generalized ordered logit regressions indicate that self-employed individuals as compared to paid employees are more likely to be satisfied with their present jobs in terms of type of work and less likely to be satisfied in terms of job security. The findings also provide many insights into the determinants of the two types of job satisfaction for both the self-employed and paid employees.
Keywords: J24; J28; L26; O52; 330; entrepreneurship; self-employment; job satisfaction; Europe; Arbeitszufriedenheit; Selbstständige; Arbeitskräfte; Vergleich; EU-Staaten